BENZENE RING GAMES: ENAM PERMAINAN INTERAKTIF SEBAGAI MEDIA PENDIDIKAN SAINS KEPADA SISWA SEKOLAH DASAR DI WILAYAH SURABAYA TIMUR - Wardani, Anggita Rara Kusuma; Mauliddawati, Vivi Tri; Ubaidillah, Nur Arif; Wijayanti, Evi; Putri, Ike Ariani Falentina (Program Kreativitas Mahasiswa - Pengabdian Kepada Masyarakat, 2013)
Proposed program student creativity Benzene Ring Games: Six Games As Interactive Media Science Education in the Elementary School Students To Kenjeran, Surabaya, is a method of learning science through game addressed to the grade 3 MI Al-Muthmainnah Surabaya where quality science education is very low in the school. This is due to the lack of facilities for science teaching and learning in these schools are only focuses on theory. Benzene Ring Games aims to improve understanding grade 3 MI Al-Muthmainnah to science that has an average value of science lowest among all grade levels. Inside there are six Benzene Ring Games sorts of games are used in materials science to provide grade 3 MI Al-Muthmainnah. After the program was applied in the Benzene Ring Games learning school in MI Al-muthmainnah, the level of understanding of grade 3 MI Al-Muthmainnah the science lesson can be increased by 62.38% and 100% students scored> 75 on the exam IPA school.